THE EFFECT OF DIRECT CHARGES TO SURPLUS ON THE MEASUREMENT OF INCOME. - Hosmer, W. A. (The Accounting Review, 1938)
Abstract The article focuses on the effect of direct charges to surplus on the measurement of income. One of the principal functions of accounting is to measure income. It is widely recognized by those who have thought on the problem that the determination of the income of a corporation in a particular year is in part an expression of judgment or rather the result of a series of judgments on varied and often complex problems. The accuracy with which income is measured is determined by the quality of judgment and the nature of the accounting principles applied in the solution of these problems. Five areas are of primary importance in income determination. These are inventory valuation, depreciation, certain features of consolidation and inter-corporate relations, the policy in writing off expenses and asset revaluations to surplus, and the handling of investment portfolios. These vary in importance depending on the circumstances of particular corporations. Frequently other factors assume major importance, such as the determination of reserve for bad debts.